PERANCANGAN ROBOT PEMINDAH BARANG LINE FOLLOWER DENGAN MAPPING BERBASIS APLIKASI MOBILE - Andini, Dilah; Sahrul Ramadhan; Ocsirendi; Saputra, Zanu (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
In the fields of industry, education, and daily life, it is not possible to be separated from the work of moving goods. To facilitate the work, a tool such as a robot is needed. A line-follower robot is a type of robot that is programmed to move along a path that has been created through a mobile application. This research designs a robot that combines line-follower technology with mobile application-based mapping, detects objects using ultrasonic sensors, and moves objects based on predetermined coordinates. The test results show that the robot can move objects. This research found that robots can increase operational efficiency while reducing human errors in moving goods.